2021
DOI: 10.1097/ico.0000000000002739
|View full text |Cite
|
Sign up to set email alerts
|

Keratoconus Management With Customized Photorefractive Keratectomy by Artificial Intelligence Ray-Tracing Optimization Combined With Higher Fluence Corneal Crosslinking: The Ray-Tracing Athens Protocol

Abstract: Purpose: The aim of this study was to report novel ray-tracing customization of surface excimer laser ablation combined with higher fluence corneal crosslinking (CXL) in the stabilization and normalization of ectasia and visual rehabilitation of progressive keratoconus. Methods: A 28-year-old man with bilateral progressive keratoconus was treated with Athens protocol: CXL combined with photorefractive surface ablation customized by a novel artificial intelligence platfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 13 publications
1
12
0
1
Order By: Relevance
“…Only a small percentage of overcorrections have been reported. 8,14 Finally, the possibility of precisely calculating the refractive contribution of the posterior corneal surface and corneal epithelium in topography-guided treatments by means of ray-tracing-guided customized ablations could make the difference by avoiding overcorrections, improving functional results, and sparing stromal tissue, as shown by pivotal studies 5,6,23 and confirmed in our case series in the long-term follow-up.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Only a small percentage of overcorrections have been reported. 8,14 Finally, the possibility of precisely calculating the refractive contribution of the posterior corneal surface and corneal epithelium in topography-guided treatments by means of ray-tracing-guided customized ablations could make the difference by avoiding overcorrections, improving functional results, and sparing stromal tissue, as shown by pivotal studies 5,6,23 and confirmed in our case series in the long-term follow-up.…”
Section: Discussionsupporting
confidence: 67%
“…The raytraced-customized corneal t-PRK has been shown to be able to solve many of the problems reported and to place itself as a possible reference standard for the personalized programming of these special treatments. 6,7,23 In our study, topography-guided custom surface ablation followed by individualized constant-fluence pachymetryguided ACXL uses a no-touch all-surface ablation with a transepithelial approach to minimize stromal consumption, taking into account the masking effect of the corneal epithelium in KC irregular corneas. The RT t-PRK plus M nomogram ACXL protocol was based on topography-guided custom ablation with ray-traced planning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Keratoconus is a progressive bilateral pathology of cornea, which is manifested by its thinning and protrusion that lead to astigmatism and deterioration of vision [ 1 ]. Different treatment options, such as spectacles and contact lenses [ 2 ], intrastromal corneal ring segments (ICRS) [ 3 7 ], keratoplasty (penetrating and deep anterior lamellar), corneal collagen cross-linking (CXL) [ 8 11 ] with topography-guided customized excimer laser ablation treatment—photorefractive keratectomy (PRK) [ 12 21 ], and combinations of the above-mentioned methods [ 16 , 21 23 ] with the application of novel ray-tracing excimer laser customization [ 24 ] could be used in patients with keratoconus, depending on its severity and grade. All treatment methods are reported to be effective and safe.…”
Section: Introductionmentioning
confidence: 99%